What Is The Effective Arabic Communication And Learning Model In Digital Learning During The Corona Crisis/ Ù…Ø§ Ù‡Ùˆ Ù†Ù…ÙˆØ°Ø¬ Ø§Ù„ØªÙˆØ§ØµÙ„ ÙˆØ§Ù„ØªØ¹Ù„Ù… Ø§Ù„Ø¹Ø±Ø¨ÙŠ Ø§Ù„ÙØ¹Ø§Ù„ ÙÙŠ Ø§Ù„ØªØ¹Ù„Ù… Ø§Ù„Ø±Ù‚Ù…ÙŠ Ø£Ø«Ù†Ø§Ø¡ Ø£Ø²Ù…Ø© ÙƒÙˆØ±ÙˆÙ†Ø§ - Alabri, Khalid Hassan (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Almost all countries in the world are helpless, and people are feared in the face of the Coronavirus, to the point that millions of schools are closed, and this impact may be more severe than the impact of the disease itself, economically and medically. This experience will be engraved in the memories of children and adults, especially teachers and students. This paper describes some hidden aspects, especially the positive ones from the pandemic. The subjects of this study were students and lecturers at King Fahd University of Petroleum and Minerals (KFUPM). By using this type of research descriptive case study. Data obtained from observations of the lecture process, student communication with lecturers, and the faculty or university are equipped with survey data to support it. The results showed that students and lecturers could adapt and commit to performance, improve electronic skills, flexibility in learning, and obtain information. In addition, the university's efforts have a positive impact on the development of distance education, the use of digital technology to increase student participation in online learning opportunities, develop faculty members, and help them reach their potential. The Deanship of Academic Development (DAD) organizes various academic development workshops, discussion forums, and symposiums involving international, national, and local experts. Also sponsors activities related to teaching, student learning, assessment, and curriculum. The staff is ready around the clock to help and solve technical problems. This makes it easier for lecturers to use programs and platforms to teach students through their accounts using university usernames and passwords (KFUPM), such as the Blackboard and Microsoft teams. Universities used electronic learning systems for teaching and exams before the Corona crisis, but the crisis made it develop faster. The course is achieved through online study, students choose Microsoft's form as the preferred system, and most students interact with lecturers after lectures. The majority see that the professor's style is attractive to students in online learning, lecturers are responsible for dealing with monotonous material, and students can have online discussions.Â Â